Pharmacokinetics and Bioequivalence Evaluation of Two Brands of Ciprofloxacin 500 mg Tablets in Iranian Healthy Volunteers - Valizadeh, H.; Hamishehkar, H.; Ghanbarzadeh, S.; Zabihian, N.; Zakeri-Milani, P. (Arzneimittelforschung, 2012)
In the present study pharmacokinetics and bioequivalence of 2 brands of ciprofloxacin 500 mg were evaluated in 24 healthy male volunteers after a single dose oral administration in an open, randomized, 2-way crossover study.Blood samples were taken before and within 12 h after the administration of the drug. Plasma concentrations of ciprofloxacin were determined by a simple HPLC method with ultraviolet detection. The used method was validated for specificity, accuracy, precision and sensitivity. The mobile phase consisted of 0.025 M phosphoric acid, acetonitrile, and triethylamine. Analytical column was 5 μm Eurosphere C8 with a Eurosphere C8 guard column. The detector wavelength was set at 278 nm and the retention time was 10 min. The pharmacokinetic parameters, including peak plasma concentrations and time needed to reach the peak were obtained directly from plasma concentration–time profiles. The area under the curve was calculated using non-compartmental methods.The Cmax of 1476.8±319.9 ng/mL and 1 423.0±278.4 ng/mL were attained in about 1.67 and 1.58 h for test and reference formulations, respectively. The mean±SD values for AUC0–∞ were 9 665.3±2 880.2 and 9 716.1±2 572.1 ng.hr/mL for test and reference formulations, respectively. The pharmacokinetics parameters AUC0-t, AUC0–∞ and Cmax were calculated for bioequivalence after log-transformation of data. The 90% confidence intervals of test/reference for AUC0-t, AUC0–∞ and Cmax were (95.6–109.9%), (91.8–106.3%) and (95.2–112.8%), respectively and all were within the bioequivalence acceptance range of 80–125%.These results indicate that 2 tested formulations are bioequivalent and thus could be prescribed interchangeably.
Keywords: bioequivalence; ciprofloxacin; pharmacokinetics; HPLC